Intercultural knowledge in action: An interactive nursing workshop on menstrual care with Munduruku women in the Kainã village (Research, Society and Development, 2025)
Nursing care focused on indigenous women requires cultural sensitivity and educational methodologies that value traditional knowledge and promote holistic well-being. This research aimed to develop an interactive nursing workshop on menstrual care, strengthening female autonomy and promoting holistic health. The methodology consisted of an experience report with a qualitative approach, using discussion circles, participatory dynamics, and dialogued lectures conducted by nursing professors and students. The project was developed in the Kainã Village, with women of the Munduruku ethnic group, seeking to promote dialogue between science and culture in menstrual care. The results demonstrated that the participants expanded their knowledge about the body and self-care, breaking taboos related to menstruation and coming to understand the importance of intimate hygiene and healthy eating during the menstrual cycle. It is concluded that participatory educational actions are effective in promoting indigenous women's health and consolidating nursing as an intercultural mediator of care.